Wisdom in Action: Village Kiai’s Leading the Charge in Non-Formal Education Advancement - Marzuki, Achmad (Al-Qalam Institue, 2023)
This research aims to analyze the process of developing non-formal education through the transformational leadership of village kiai. Non-formal education plays a crucial role in community development, particularly for individuals who lack access to formal education. In this context, village kiai serve as key figures who not only provide religious guidance but also act as agents of change in fostering education and social development. Their leadership style influences community participation and enhances the learning process in non-formal educational settings. This study employs a qualitative case study approach to explore the leadership practices of village kiai in managing and advancing non-formal education. Data collection methods include interviews, observations, and documentation studies. The collected data is then analyzed using the interactive model of Miles and Huberman, which consists of data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that the transformational leadership of village kiai functions as a dynamic force in achieving the vision and mission of non-formal education. Their ability to mobilize the community facilitates knowledge development among individuals, fostering a sense of collective responsibility. The effectiveness of their leadership is characterized by four key dimensions: charismatic influence, intellectual stimulation, individualized consideration, and inspirational motivation. Through these characteristics, village kiai successfully inspire, educate, and guide their communities in engaging with non-formal education initiatives. The findings also offer a framework for developing leadership strategies that can enhance the effectiveness of non-formal education in various socio-cultural contexts.